Zoonym phrases (Ta'limning zamonaviy transformatsiyasi, 2024)
Zoomorphic phrases—expressions involving animal-related metaphors—are deeply woven into languages worldwide. Such phrases reflect human characteristics and emotions through animal behaviors, creating vivid, relatable imagery. By studying these expressions, we uncover cultural perceptions of animals and see how they inform our understanding of human nature.Zoomorphic phrases leverage animals to illustrate human qualities in a symbolic way. These phrases are not literal but carry meanings derived from popular associations with each animal. For instance, the phrase "as sly as a fox" portrays cunning behavior, as foxes are often perceived as intelligent but tricky. Zoomorphic expressions connect language with the natural world, creating rich, culturally embedded expressions.